2006
DOI: 10.1038/sj.jp.7211594
|View full text |Cite
|
Sign up to set email alerts
|

Hyperglycemia in extremely low birth weight infants in a predominantly Hispanic population and related morbidities

Abstract: Objective: This study describes the incidence, correlates and subsequent morbidities of hyperglycemia, a highly prevalent condition in extremely low birth weight (ELBW) infants.Study design: A retrospective chart review of 169 infants with birth weight (BW)<1000 g was conducted. Hyperglycemia was defined as plasma glucose level X150 mg/dl during the first 2 weeks of life. Data were analyzed by logistic regression, multivariate analysis and Fisher exact test.Results: Overall, 88% of the study sample developed h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

11
107
2
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 125 publications
(123 citation statements)
references
References 30 publications
(33 reference statements)
11
107
2
1
Order By: Relevance
“…Kao et al 4 found no significant association of hyperglycemia with total number of days of mechanical ventilation among survivors and length of stay for survivors not transferred to another facility. Blanco et al 5 after adjusting for gestational age, birth weight, postnatal steroids and sepsis, showed an inverse association between hyperglycemia and chorioamnionitis (OR 0.10, 95% CI 0.01 -0.64). Blanco et al 5 also found an association between hyperglycemia and ROP (OR 4.6, 95% CI 1.1-8.9).…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…Kao et al 4 found no significant association of hyperglycemia with total number of days of mechanical ventilation among survivors and length of stay for survivors not transferred to another facility. Blanco et al 5 after adjusting for gestational age, birth weight, postnatal steroids and sepsis, showed an inverse association between hyperglycemia and chorioamnionitis (OR 0.10, 95% CI 0.01 -0.64). Blanco et al 5 also found an association between hyperglycemia and ROP (OR 4.6, 95% CI 1.1-8.9).…”
mentioning
confidence: 99%
“…Blanco et al 5 after adjusting for gestational age, birth weight, postnatal steroids and sepsis, showed an inverse association between hyperglycemia and chorioamnionitis (OR 0.10, 95% CI 0.01 -0.64). Blanco et al 5 also found an association between hyperglycemia and ROP (OR 4.6, 95% CI 1.1-8.9). There was no association between hyperglycemia and birth weight, sepsis, death, prolonged hospital stay, bronchopulmonary dysplasia, intraventricular hemorrhage or postnatal steroid exposure.…”
mentioning
confidence: 99%
See 3 more Smart Citations